2015
DOI: 10.1371/journal.pone.0118846
|View full text |Cite|
|
Sign up to set email alerts
|

Tigers of Sundarbans in India: Is the Population a Separate Conservation Unit?

Abstract: The Sundarbans tiger inhabits a unique mangrove habitat and are morphologically distinct from the recognized tiger subspecies in terms of skull morphometrics and body size. Thus, there is an urgent need to assess their ecological and genetic distinctiveness and determine if Sundarbans tigers should be defined and managed as separate conservation unit. We utilized nine microsatellites and 3 kb from four mitochondrial DNA (mtDNA) genes to estimate genetic variability, population structure, demographic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 75 publications
1
26
1
Order By: Relevance
“…Similarly, the observed heterozygosity in the tiger population of the Bangladesh Sundarbans (Ho = 0.37) is also lower than the tiger population in the Indian Sundarbans (Ho = 0.49; n=13; Singh et al, 2015) and Northeast India (Ho = 0.47; n=15; Borthakur et al 2013). The overall lower levels of allele diversity and heterozygosity in the Sundarbans population could be attributed to the fact that this population has long been isolated from the nearest tiger populations of Similipal tiger reserve in West Bengal of India, thereby completely wiped out any chance of gene flow between the populations.…”
Section: Genetic Diversitymentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, the observed heterozygosity in the tiger population of the Bangladesh Sundarbans (Ho = 0.37) is also lower than the tiger population in the Indian Sundarbans (Ho = 0.49; n=13; Singh et al, 2015) and Northeast India (Ho = 0.47; n=15; Borthakur et al 2013). The overall lower levels of allele diversity and heterozygosity in the Sundarbans population could be attributed to the fact that this population has long been isolated from the nearest tiger populations of Similipal tiger reserve in West Bengal of India, thereby completely wiped out any chance of gene flow between the populations.…”
Section: Genetic Diversitymentioning
confidence: 89%
“…For instance, radio-collaring studies have revealed that tigers rarely cross the rivers wider than 400 m in India Sundarbans (Naha et al 2016) as well as 600 m in Bangladesh Sundarbans (Barlow 2009), suggesting that tiger movement might have been compromised by wide rivers in this mangrove forests. Several studies have highlighted the morphological adaptation (Barlow et al 2010) and genetic distinctiveness (Singh et al 2015) of the Sundarbans tigers, however none have examined the effect of barriers on the fine-scale genetic structure of the population. Understanding how landscape barriers facilitate or deter gene flow is a high priority management need for an endangered population surviving in a changing forest habitat (Sork and Waits 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, most genetic studies conducted on the Bengal tiger have been either in some way focused on the global status [41, 42] or were carried out in different tiger landscapes or regions, such as the Central and Peninsular [43, 44], Western (e.g. Ranthambhore Tiger Reserve) [45] and Sundarbans [46]. Despite the current knowledge of the tiger’s ecology, there is no information on the gene flow and genetic structure of the tiger population especially in WTAL, which holds the largest number of tigers [32], except from mitochondrial (mtDNA) markers [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…This unique landscape is regarded as a UNESCO World Heritage site, shared by both India and Bangladesh. This region is well known for containing numerous endemic, ecologically, economically important flora and fauna and is an important habitat for many Endangered and distinct evolutionary significant unit of Bengal tiger (Singh et al 2015). It is reported that the alteration of biogeography, directly influence the population structure through species dynamics, colonization, and isolation (Costello et al 2003).…”
Section: Resultsmentioning
confidence: 99%